2011
DOI: 10.1371/journal.pone.0019708
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Prophage DNA Adenine Methyltransferase Genes in Different Drosophila-Wolbachia Associations

Abstract: Wolbachia is an obligatory intracellular bacterium which often manipulates the reproduction of its insect and isopod hosts. In contrast, Wolbachia is an essential symbiont in filarial nematodes. Lately, Wolbachia has been implicated in genomic imprinting of host DNA through cytosine methylation. The importance of DNA methylation in cell fate and biology calls for in depth studing of putative methylation-related genes. We present a molecular and phylogenetic analysis of a putative DNA adenine methyltransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…One hypothesis is that a WO DNA methyltransferase gene may encode the mod and/or resc factors of CI [37]. This theory fits well with the fact that sperm DNA appears to be modified in the hosts of mod+ Wolbachia strains and that DNA methylation is altered during feminization of the leafhopper species Zyginidia pullula when infected with Wolbachia , although methylation patterns have not yet been investigated in CI [39].…”
Section: Involvement Of Wo In Reproductive Parasitismmentioning
confidence: 91%
See 1 more Smart Citation
“…One hypothesis is that a WO DNA methyltransferase gene may encode the mod and/or resc factors of CI [37]. This theory fits well with the fact that sperm DNA appears to be modified in the hosts of mod+ Wolbachia strains and that DNA methylation is altered during feminization of the leafhopper species Zyginidia pullula when infected with Wolbachia , although methylation patterns have not yet been investigated in CI [39].…”
Section: Involvement Of Wo In Reproductive Parasitismmentioning
confidence: 91%
“…Another theory, the Goalkeeper Model, posits that only two factors exist, but that their concentration or activity level accounts for incompatibility between some strains [36]. In any case, these intricate CI patterns have enabled a search for correlations between strain compatibility and WO, although the results have been somewhat contradictory [12,18,37,38]. …”
Section: Involvement Of Wo In Reproductive Parasitismmentioning
confidence: 99%
“…2). Additionally, it was hypothesized that an adenine-specific MTase plays a role in regulating the cell cycle interactions of Drosophila and the intracellular symbiont Wolbachia pipientis, as prophages have been found only in strains that are in a symbiotic relationship (70), further highlighting that phage orphan MTases have roles similar to the roles of MTases found in bacterial cells.…”
Section: Bacteriophage Mtases Possible Function and Prevalencementioning
confidence: 99%
“…The currently strongest evidence for a role of epigenetics was found by Negri et al [2009] who showed that Wolbachia interferes with host sexual differentiation in the leafhopper Z. pullula by disrupting methylation patterns and genetic imprinting. In Drosophila species, Wolbachia prophage DNA adenine methyltransferase genes might be involved in the modification or rescue process of CI [Saridaki et al, 2011]. These studies are first indications for a role of epigenetics in host manipulation, but we are only at the beginning of elucidating the precise molecular and biochemical pathways involved.…”
Section: Discussionmentioning
confidence: 99%